LES MARCHES FRONTALIERS: FACTEURS ET TEMOINS D’UN INVESTISSEMENT COLLECTIF MARCHAND ET PUBLIC - Atta Koffi; Nama Laurent Anzan; Dongo Koffi René; Gogbé Téré (European Scientific Journal, ESJ, 2013)
Since the middle of the years 1980, the borders of State became places of commercial excitement, animated at the same time by the far-off flows and the small cross-border traffics. Following the example of these cross-border spaces, the one of Indénié-Djuablin located in the East of Ivory Coast, that shelters several urban and rural markets puts rhythm into the commercial activities. These commercial places which mark out the frontier line between Ivory Coast and Ghana are invaded by several actors who play very important part in the development of the frontier site. The following study has for main aim to measure the investments achieved in the cross-border space allowing the improvement of the level and the framework of the life of the populations. So observations and interviews were carried out in twelve (12) frontier localities as well on the side of Ivory Coast as on the Ghanaian side. In spite of the commercial turmoil under the protection of the border, the socio-educational, collective equipment and other investments in the real estate noted are mainly the work of the public authorities with a tiny participation of some commercial actors. The infrastructural problems, of insecurity and facilities are as many hindrances to the dynamism to the border commercial places. It would therefore be advisable to the main actors to invest in the country-border helping thus the public authorities to improve their condition and the living environment.